2014
DOI: 10.1186/1297-9716-45-57
|View full text |Cite
|
Sign up to set email alerts
|

Identification and genotyping of feline infectious peritonitis-associated single nucleotide polymorphisms in the feline interferon-γ gene

Abstract: Feline infectious peritonitis (FIP) is an immune-mediated, highly lethal disease caused by feline coronavirus (FCoV) infection. Currently, no protective vaccine or effective treatment for the disease is available. Studies have found that some cats survive the challenge of virulent FCoV isolates. Since cellular immunity is thought to be critical in preventing FIP and because diseased cats often show a significant decrease in interferon-γ (IFN-γ) production, we investigated whether single nucleotide polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 50 publications
2
31
2
Order By: Relevance
“…These type I and II interferons have major antiviral roles in the innate immune system. IFN-g in particular has been of interest in FIP, as levels of this potentially protective cytokine tend to be low in the peripheral blood of diseased animals and host gene polymorphisms have been identified that may contribute to resistance against the disease (Gelain et al, 2006;Hsieh and Chueh, 2014). Similarly to the apparent lack of impact of mediator levels on the presence of lesions or effusions in FIP, this suggests that MLN IFN production has a more local effect.…”
Section: Discussionmentioning
confidence: 99%
“…These type I and II interferons have major antiviral roles in the innate immune system. IFN-g in particular has been of interest in FIP, as levels of this potentially protective cytokine tend to be low in the peripheral blood of diseased animals and host gene polymorphisms have been identified that may contribute to resistance against the disease (Gelain et al, 2006;Hsieh and Chueh, 2014). Similarly to the apparent lack of impact of mediator levels on the presence of lesions or effusions in FIP, this suggests that MLN IFN production has a more local effect.…”
Section: Discussionmentioning
confidence: 99%
“…The -336AG/GG genotype was associated with lower standardized lactatedehydrogenase (LDH) levels compared with the '-336AA' genotype carrying patients with a 60% chance of having a poorer prognosis because of higher LDH levels. In cats, several SNPs have been described in CD209, TNF-a [51] and IFN-g [52] genes. They were found to be associated with the outcome of FCoV infection, that is, with the susceptibility for or the resistance to Feline Infectious Peritonitis (FIP), an immune-mediated, highly lethal disease without effective therapy and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism for this phenomenon is not completely understood, but it is assumed that immunosuppression favors the generation of escape mutants and thereby, the probability of clinical manifestation of FIP. Furthermore, genetic predisposition to FIP was suggested (Golovko et al, 2013;Hsieh and Chueh, 2014;Pedersen, 2009;Pesteanu-Somogyi et al, 2006;Wang et al, 2014;Worthing et al, 2012).…”
Section: Feline Infectious Peritonitis Virusmentioning
confidence: 99%